Effects of dietary protein/energy ratio and water temperature on growth performance, digestive enzymes activity and non‐specific immune response of spotted seabass (Lateolabrax maculatus). (28th August 2020) - Lu, Kang‐Le; Cai, Lin‐Sen; Wang, Ling; Song, Kai; Zhang, Chun‐Xiao; Rahimnejad, Samad
Abstract: This study investigated the effects of dietary protein/energy (P/E) ratio and water temperature on growth performance, blood biochemistry, digestive enzymes activity and innate immunity of spotted seabass ( Lateolabrax maculatus ). Six diets were formulated to contain two protein (440 and 470 g/kg) and three lipid levels (80, 110 and 140 g/kg) with P/E ratios of 22.31, 23.27, 23.47, 24.05, 24.35 and 25.55 g/MJ. Each diet was fed to two different sets of fish (2.67 ± 0.01 g) kept at low temperature (27°C; LT) or high temperature (33°C; HT). Triplicate groups of fish were fed to apparent satiation three times daily for 8 weeks. The highest weight gain values were obtained at P/E ratios of 24.35 (470 g/kg protein and 110 g/kg lipid) and 23.47 (470 g/kg protein and 140 g/kg lipid) at LT and HT, respectively. Feed conversion ratio (FCR) was also significantly influenced by dietary P/E ratios where the lowest FCR was found in fish received the diet with P/E of 22.31 and kept at LT. Intestinal protease, amylase and lipase activities were neither affected by dietary P/E ratios nor water temperature. Significantly higher hepatic citrate synthase and succinate dehydrogenase activities were detected in LT groups. All serum innate immune parameters including lysozyme, complements 3 and 4, immunoglobulin and alkaline phosphatase were decreased by increasing water temperature. The findings in this study showed that optimal P/E ratios for spotted seabass at 27 and 33°C are 22.31 and 23.47 g/MJ, respectively, and that high temperature induces retarded growth and suppressed immune function.